ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF DALAM MUATAN IPA DI KELAS 6 SD N 02 PALEMBANG - Yolanda; Dwi Cahaya Nurani; Mazda Leva Okta Safitri (Jurnal Literasi Pendidikan Dasar, 2023)
This study aims to analyze the needs of interactive video learning media in Natural Science in grade 6 SDN 02 Palembang. The research method used descriptive qualitative through observation and interviews techniques toward 3 teachers of grade 6. The results of the study showed that teachers need interactive video learning media that can facilitate understanding of science concepts more easily and effectively. This is due to the lack of interactive and technology-based learning resources in the school environment. It is hoped that interactive video learning media can be an interesting and effective teaching alternative to improve the Natural Science learning outcomes of students. Therefore, the development of interactive video learning media needs to be considered in preparing science learning plans in grade 6 SDN 02 Palembang.